Adapting to ulcerative colitis to try to live a 'normal' life: a qualitative study of patients' experiences in the Midlands region of England. Issue 8 (21st August 2017) - McMullan, Christel; Pinkney, Thomas D; Jones, Laura L; Magill, Laura; Nepogodiev, Dmitri; Pathmakanthan, Shri; Cooney, Rachel; Mathers, Jonathan M
Abstract : Objective: To provide a framework that is able to categorise whether patients are able to adapt to and lead a 'normal' life with ulcerative colitis (UC) and to detail the factors that influence this. Design: Qualitative research study using in-depth semi-structured interviews. Setting: Four clinical sites in the West and East Midlands regions of England. Participants: 28 adult patients diagnosed with UC for years between 1 and 22. Results: Medication was rarely sufficient for patients to adapt to UC and live as 'normal' a life as possible. Virtually all patients tested and adopted non-medical adaptation methods to improve physical and psychological well-being, to help them carry on working and to prevent embarrassment. In addition, some patients benefited from outside support providing them with practical, emotional and/or financial help. In conjunction with adaptation strategies and the time to adapt, this meant that some patients with severe clinical disease were able to maintain a sense of normality in life. Patients reported that clinicians were not always receptive to discussion of the broader context of life with UC. Conclusions: Patients' experience of UC and their ability to adapt in order to maintain a sense of normality in life is a complex interplay of symptoms, adaptation strategies and outside support. Over time patients test out a variety of non-medical adaptation strategies. Awareness of this may help clinicians and researchers to understand patients' views on the role of medical and other therapies. Further research around the utility of this framework in clinical practice and research is now required. Trial registration number: ISRCTN56523019, results.